2016
DOI: 10.1111/bph.13502
|View full text |Cite
|
Sign up to set email alerts
|

Obestatin as a key regulator of metabolism and cardiovascular function with emerging therapeutic potential for diabetes

Abstract: *These two authors contributed equally to this work.Obestatin is a 23-amino acid C-terminally amidated gastrointestinal peptide derived from preproghrelin and which forms an α helix. Although obestatin has a short biological half-life and is rapidly degraded, it is proposed to exert wide-ranging pathophysiological actions. Whilst the precise nature of many of its effects is unclear, accumulating evidence supports positive actions on both metabolism and cardiovascular function. For example, obestatin has been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 190 publications
(240 reference statements)
2
40
0
1
Order By: Relevance
“…Obestatin, a gastrointestinal peptide discovered in 2005, is derived from the same precursor as ghrelin and inhibits food intake in mammals (Cowan et al, 2016). In grass carp, although IP injections of an obestatin-like peptide alone do not affect food intake or the expression levels of NPY, CART, or POMC, when co-injected with ghrelin, it blocks ghrelin-induced stimulation of appetite and up-regulation of expressions of NPY and NPY receptors (Yuan et al, 2015), suggesting that obestatin might inhibit the ghrelin system in Cypriniformes.…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…Obestatin, a gastrointestinal peptide discovered in 2005, is derived from the same precursor as ghrelin and inhibits food intake in mammals (Cowan et al, 2016). In grass carp, although IP injections of an obestatin-like peptide alone do not affect food intake or the expression levels of NPY, CART, or POMC, when co-injected with ghrelin, it blocks ghrelin-induced stimulation of appetite and up-regulation of expressions of NPY and NPY receptors (Yuan et al, 2015), suggesting that obestatin might inhibit the ghrelin system in Cypriniformes.…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…Several mechanisms may explain the possible link between obestatin and clinical outcomes in our population, while most of them supported by experimental studies indicate potential cardio-protective properties of obestatin [19, 20]. Obestatin was found to be beneficial in cardiomyocyte injury induced by ischemia-reperfusion in vivo and in vitro [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Even though these effects on feeding behavior and gastrointestinal motion have been subsequently disputed and the precise identity of its cognate receptor(s) is still a matter of debate (5), obestatin indisputably exerts a variety of effects in different cell types, including pancreatic b-cells, where it increases survival and proliferation by inhibiting apoptosis and inflammation (6,7). In line with these actions, other favorable effects of obestatin have been observed on glucose and lipid metabolism, such as increased glucose uptake and insulin sensitivity as well as inhibition of lipolysis in human adipocytes (7,8).Interestingly, in addition to its helpful metabolic properties, obestatin has been shown to provide vascular benefits in experimental models. Thus, in rat aorta and the superior mesenteric artery, Agnew et al (9) have demonstrated that obestatin favorably affects endothelial function, inducing nitric oxide (NO)-dependent relaxation via an adenylate cyclase-linked GPCR.…”
mentioning
confidence: 91%
“…Even though these effects on feeding behavior and gastrointestinal motion have been subsequently disputed and the precise identity of its cognate receptor(s) is still a matter of debate (5), obestatin indisputably exerts a variety of effects in different cell types, including pancreatic b-cells, where it increases survival and proliferation by inhibiting apoptosis and inflammation (6,7). In line with these actions, other favorable effects of obestatin have been observed on glucose and lipid metabolism, such as increased glucose uptake and insulin sensitivity as well as inhibition of lipolysis in human adipocytes (7,8).…”
mentioning
confidence: 99%